Formation of multilayer graphene cells in liquid methanol using a dotted–pulsed laser via an additive technique. (October 2022) - Lin, Yu-Wei; Hsu, Tzu-Yuan; Hsu, Chen
Abstract: The formation of multilayer graphene cells (MGCs) in liquid methanol is studied using a dotted–pulsed laser via an additive technique. The MGCs are formed using the burning methanol processes. Thus, the resultant carbons are formed via decomposition and resolidification. The resultant microstructures were characterized using scanning electron microscopy and X-ray diffraction. The carbon bond statuses were determined using Raman spectroscopy. The electrical conductivities were measured under a He atmosphere. These results show that the resultant microstructures and their properties are similar to those of reduced graphene oxide. The proposed method using a dotted–pulsed laser via additive technique is a simple way to produce MGCs in liquid methanol.